2007
DOI: 10.1007/s11695-007-9232-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy — Influence of Sleeve Size and Resected Gastric Volume

Abstract: Early weight loss results were not different between the groups, but after 2 years the more restrictive LSG (groups 2, 3) results were significantly better than in patients without calibration. A removed gastric volume of <500 cc seems to be a predictor of failure in treatment or early weight regain. A statistically significant improved health status and quality of life were registered for all groups. The general introduction of LSG as a one-stage restrictive procedure in the bariatric field can be considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
212
2
18

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 396 publications
(250 citation statements)
references
References 18 publications
11
212
2
18
Order By: Relevance
“…Also, they showed a reduction in the operative risk (ASA score) after LSG. They proved that LSG effec-tively downstages patients to a lower-risk group as Cottam et al [41] and Weiner et al [47] also reported, and effectively resolved or improved co-morbidities as many other teams have also demonstrated ( Table 1).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Also, they showed a reduction in the operative risk (ASA score) after LSG. They proved that LSG effec-tively downstages patients to a lower-risk group as Cottam et al [41] and Weiner et al [47] also reported, and effectively resolved or improved co-morbidities as many other teams have also demonstrated ( Table 1).…”
Section: Discussionmentioning
confidence: 82%
“…LSG has demonstrated weight-loss results comparable to LRYGB and LBPD-DS but with a lower morbidity profile, associated with improvement of health status and resolution of co-morbidities such as diabetes, hypertension, OSA and dyslipidemia [16,18,38,41,44,45,47,48]. Silecchia et al [44] showed that in 41 super-obese patients (9 patients with BMI > 60 kg/m ) following LSG, 60% of major comorbidities were resolved and 24% improved, 57.8% of patients were co-morbidity-free and 31.5% had only one major co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations